2006
DOI: 10.1016/j.pbb.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

An autoradiographic analysis of rat brain nicotinic receptor plasticity following dietary choline modification

Abstract: Choline is known to be involved with numerous physiological functions of the nervous system and also acts as a direct acting agonist of α7 nicotinic acetylcholine receptors (nAChRs). The purpose of this study was to conduct a brain region-specific evaluation of changes in nAChR subtype expression following dietary choline modification. In addition, we assessed changes in body weight, food/water intake, as well as changes spatial learning (Morris Water Maze) in response to dietary choline modification. Male Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Increases in the number of α7 receptors could have increased the release of GABA, thus increasing inhibition of pyramidal cell firing in response to the second stimulus. Increases in α-bungarotoxin binding have been observed with subchronic (2 weeks; Guseva et al 2006) or chronic dietary choline supplementation in adult rats (Coutcher et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the number of α7 receptors could have increased the release of GABA, thus increasing inhibition of pyramidal cell firing in response to the second stimulus. Increases in α-bungarotoxin binding have been observed with subchronic (2 weeks; Guseva et al 2006) or chronic dietary choline supplementation in adult rats (Coutcher et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Cholineevoked electrophysiological responses from single cells or hippocamlpal slices are blocked by either methyllycaconitine or ␣ bungarotoxin (BTX), selective ␣7 antagonists (Alkondon et al, 1997;Albuquerque et al, 1998;Fayuk and Yakel, 2004). Dietary supplementation with choline results in selective increases the density of ␣7 nicotinic receptors in multiple brain regions, consistent with the actions of a nicotinic cholinergic agonist (Morley et al, 1977;Coutcher et al, 1992;Guseva et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Previous research has shown that adult rats treated prenatally with supplemental choline, a selective agonist of α7 nicotinic acetylcholine receptors (α7-nAChR - Alkondon et al, 1997Alkondon et al, , 1999Guseva et al, 2006), exhibit enhanced attention and precision in the temporal control of responding when trained in a peak-interval (PI) timing procedure (Meck and Williams 1997a, b). This enhancement can be related to an increase in rats' sensitivity to the inhibitory effects of a signaled delay to reinforcement and the associated resetting of an internal clock by the delivery of reinforcement (Matell and Meck 1999;Cheng et al 2006).…”
Section: Introductionmentioning
confidence: 99%